Characters of Actors Implementing the Internal Quality Assurance System (SPMI) in Secondary Education Services (Study Of Good And Poor Performing High Schools in Kupang City) - BANA, Isak; NURSALAM, Nursalam; SAYRANI, Laurensius P. (PT Batara Swastika Harati, 2024)
This research chose the high school level because it is the last level before entering higher education (PT), which is different from the vocational school level where apart from going to PT you can also directly enter the world of work or industry. The city of Kupang was chosen because it is still a barometer of education in NTT Province. This research used a qualitative approach with 81 informants. Primary and secondary data were obtained through interviews, observation and literature review. Data were analyzed using techniques from Miles, Huberman, and Saldana (2014) which included data condensation, data presentation, and drawing conclusions or verification. The research results show that the character of the actors implementing the Internal Quality Assurance System (SPMI) in secondary education services at high schools in Kupang City, whether performing well or poorly, was analyzed using the grid model from Bryson (2004). Findings show that: High Interest – Low Power (Subjects): Teachers involved in the school education quality assurance team (TPMPS) at SMAN 2 Kupang and SMAN 6 Kupang do not understand their role in the team. High Interest – High Power (Players): Supervisors from the provincial education office and school principals as managers in educational units do not know the SPMI team, but know the school development team (TPS) at SMAN 2 and the curriculum development team (TPK) at SMAN 6 Kupang. Low Interest – High Power (Context Setters): Committees and administration understand their role as directors and administrative staff but do not know the TPK team.